2015
DOI: 10.1111/joor.12308
|View full text |Cite
|
Sign up to set email alerts
|

Dental implants inserted in male versus female patients: a systematic review and meta‐analysis

Abstract: The aim of this meta-analysis was to test the null hypothesis of no difference in the failure rates, marginal bone loss (MBL) and post-operative infection for implants inserted in male or female patients, against the alternative hypothesis of a difference. An electronic search without time or language restrictions was undertaken in December 2014. Eligibility criteria included clinical human studies, either randomized or not. Ninety-one publications were included, with a total of 27,203 implants inserted in men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 102 publications
(104 reference statements)
4
22
0
Order By: Relevance
“…Moreover, the result is also supported by previous publications: A meta-analytic investigation31 of 91 studies with 52 357 implants registered a 21% increase on the implant failure rate for male patients while assessing the outcome of dental implantsupported restorations. Moreover, the result is also supported by previous publications: A meta-analytic investigation31 of 91 studies with 52 357 implants registered a 21% increase on the implant failure rate for male patients while assessing the outcome of dental implantsupported restorations.…”
supporting
confidence: 84%
“…Moreover, the result is also supported by previous publications: A meta-analytic investigation31 of 91 studies with 52 357 implants registered a 21% increase on the implant failure rate for male patients while assessing the outcome of dental implantsupported restorations. Moreover, the result is also supported by previous publications: A meta-analytic investigation31 of 91 studies with 52 357 implants registered a 21% increase on the implant failure rate for male patients while assessing the outcome of dental implantsupported restorations.…”
supporting
confidence: 84%
“…No conclusion could be made regarding marginal bone loss due to the lack of studies. 44 In conclusion, the statistical analyses revealed that some factors related to the implant, patient, and clinical procedures affected the marginal bone remodeling at the hydrophilic and moderately rough implants in the present study. Since a relatively low number of implants were placed in the study, it is likely that the different factors interplayed and affected the statistical outcome, which has to be interpreted with caution.…”
Section: A Frequency Distribution Of Bone Level Measurements After 5 supporting
confidence: 46%
“…In a meta‐analysis study on the effect on gender in implant patients, Chrcanovic et al found more implant failures in male than in female. No conclusion could be made regarding marginal bone loss due to the lack of studies …”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies on the literature reported implant failure rates ranging from 4 up to 34% (Chrcanovic et al. ). Briefly, after the implant insertion, water molecules and fluids containing protein from saliva, gingival crevicular fluid and serum bind to the implant surface incorporating ions and forming a pellicle rich in protein, which serves as basis for the development of the oral biofilm (Dorkhan et al.…”
mentioning
confidence: 99%
“…Recent studies showed that peri-implantitis occurs in 20% of the implants with an average time in function varying between 5 and 11 years (Mombelli et al 2012) and is closely related to bacterial biofilm formation on the implant surface (Teughels et al 2006). In addition, studies on the literature reported implant failure rates ranging from 4 up to 34% (Chrcanovic et al 2015). Briefly, after the implant insertion, water molecules and fluids containing protein from saliva, gingival crevicular fluid and serum bind to the implant surface incorporating ions and forming a pellicle rich in protein, which serves as basis for the development of the oral biofilm (Dorkhan et al 2012).…”
mentioning
confidence: 99%